Performance profiling of UV-grafted forward osmosis polyethersulfone membrane using multivariate classical scaling technique - Ahmad Fikri Hadi Abdul, Rahman; Mohd Yusri, Mohd Yunus; Tengku Siti Laila Maisarah, Tengku Ahmad Nasaruddin; Noorlisa, Harun; Mazrul Nizam, Abu Seman (IOP Publishing Ltd, 2019)
In this work, Classical Scaling (CMDS) method was used to develop a set of membrane profile performance for various types of UV-grafted polyethersulfone (PES) membrane. Previously, there is no such profiling has been considered. The main motivation of the profiling is to determine what is the most preference impact factor which significantly influence the membrane strength during application. Initially, nine (9) different samples of modified PES membranes were prepared mainly by adopting numerous characterization parameters of acrylic acid monomer concentration and grafting time. Three (3) performance indicators namely water permeability (A), solute permeability (B) and structural parameter (S) were used as representing the foundation of membrane performance profile. In particular, the Euclidean and City-block scales were utilized to build up the multivariate profile based on two dimension configurations. The key finding suggests that the modified membranes were easily clustered based on its grafting mechanism. From the general observation on the compressed CMDS dimensional space, samples that fall above the x-axis in Euclidean scale configuration and those scattered samples in the City-block scale have relatively larger pores. Thus, the CMDS profiling tends to favor the pore size as the dominant impact factor in characterizing the membrane performance based on the three specified parameters that investigated.